Climate Variability and Societal Dynamics in Pre-Colonial Southern African History (AD 900-1840): A Synthesis and Critique. (1st August 2014) - Hannaford, Matthew J.; Bigg, Grant R.; Jones, Julie M.; Phimister, Ian; Staub, Martial
Abstract : The role of climate variability in pre-colonial southern African history is highly disputed. We here provide a synthesis and critique of climate-society discourses relating to two regionally-defining periods of state formation and disaggregation. The first period involves the eleventh-thirteenth century development of socio-political complexity and the rise of southern Africa's first state, Mapungubwe, followed by its collapse and the shift in regional power to Great Zimbabwe. The later period encompasses the early-nineteenth century difaqane/mfecane mass migrations, violence and ensuing state-building activity. To further our assessment, we consider the wider contentious issues of climate causation and determinism in a regional context, but dispute suggestions of paradigm shift towards simplistic environmental collapse. Nevertheless, we specifically point to ambiguities in palaeoclimate records, a narrative tendency toward monocausal explanations and a lack of integration among the literature as reasons for a sustained divergence in interpretation regarding the significance of climate. We move on to discuss the potential of integrative approaches to illuminate understanding of the complex interactions between past climate variability and human activity. In order to do so, we highlight interlinked concepts such as vulnerability and resilience as key for bridging the gap between the natural and social sciences. To conclude, we point to future climate-society priorities and ways forward in the form of research areas, data prospects and questions.